Auditing Regulations of Environmental Reporting of Oil Companies - T. A. Dudko (Учёт. Анализ. Аудит)
The article is devoted to the study of the theoretical foundations and normative regulations of the audit of environmental reporting of oil companies in Russia. The article presents the materials of the analysis conducted by the author of the practice of disclosing information on the environmental aspects of activities in the reporting of oil companies, as well as the main provisions and legal framework governing the audit of environmental reporting. The research revealed the problem of the lack of a unified and single standard for regulating non-financial reporting, which makes it difficult for users to analyze such reports and analysis. Generalization and comparison were the methodological research tools. The theoretical and political significance of the study lies in justifying the need to develop a regulatory framework to regulate the requirements for the preparation of non-financial reporting and its auditing to improve the comparison of data by the stakeholders. The study is of interest primarily to government agencies and to the Committee for Standardization of the Russian Federation in improving the legislative regulation of accounting and non-financial reporting.